دور السياحة البيئية في تحقيق التنمية المستدامة - علاوي عبد القادر; الزاوي مهدي محمد; علاوي صفية (جامعة عمار ثليجي الاغواط, 2022)
The study aims to highlight the meaning and concept of ecotourism and sustainable tourism development and the requirements for its application, in order to reach the standards of sustainable tourism development through which tourism development experiences can be evaluated, describing the current situation of ecotourism in Algeria. We have concluded through the results that the concept of tourism development is not a stable state of balance between achieving economic benefits and protecting the environment, so that the concept of best environmental practice may differ from one region to another in terms of different problems and conditions of development in each region, which leads to a different concept of sustainable tourism development.